ANALYSIS OF COMPERATIVE LANGUAGE STYLE AND LINKING LANGUAGE STYLE ON THE CARS 1 MOVIE SCRIPT - Fernando Sahat Halomoan Rajagukguk; Rina Octavia Simarmata; Harpen H. P. Silitonga (Jurnal Scientia, 2023)
This research aims to describe: (1) What language styles are used in the movie "Cars 1." This type of research is qualitative in nature. The data subject in this research is the movie "Cars 1." The research object consists of comparative language styles and linkage language styles in "Cars 1" movie. The data source for this research is obtained through other individuals or documents. The data for this research are the analysis of comparative language styles and linkage language styles in "Cars 1" movie. Data are collected using library research techniques, reading techniques, note-taking techniques, and summarization techniques. The instrument used is the researcher themselves, assisted by data cards. The data analysis technique employed in this research is content analysis. Data validity is ensured through data triangulation.